Gartner Model and Partial Least Square Regression for Evaluation the Maturity Level E-Government Public Services in Provincial Papua - Moh. Rahmat Irjii Matdoan; Rasna Rasna; Rostini Anwar; Muhammad Ridwan Rumasukun; Gustaf Griapon (Universitas Raharja, 2023)
Governance in Indonesia in the era of technology 4.0 is required to follow changes and accommodate every community's aspirations quickly. The level of participation and become an advantage of E-government in breaking the divide between the government and the people in Indonesia. The level of public participation that continues to increase if it is open makes E-Government much needed in Indonesia. However, there are still many government information systems that are created and implemented that do not work optimally both in regional and central governments. The purpose of this research is to provide basic data, follow-up data, and all that is needed for the development of an E-Government strategy. Measuring the maturity level of E-government is needed to determine the extent of the implementation of E-Government in Papua Province. The model used to measure the level of maturity in the study is the Gartner Model. Gartner's model suggests four critical phases of e- government evolution: web presence, interaction, transaction, and transformation. The research methodology uses a questionnaire and the calculation uses the average score of each dimension. To find out the relationship between the dimensions and the criteria used the Partial Least Square method. The results of the research that the maturity level of E-Government is 4.06 (predictable process). The dimensions of transformation and usability affect public participation in using e-government in Papua Province.